Hubungan Nilai Mean Platelet Volume (MPV) dengan Derajat Sepsis - Andi Raga Ginting; Endang Sembiring; Armon Rahimi (Fakultas Kedokteran USU, 2016)
Background : Sepsis is a major disease that affects millions of people worldwide every year. Almost all organs and systems were affected by sepsis. Hemostatic system is also affected. Easily accessible, inexpensive, and widely used laboratory tests that shows sepsis and the severity are important.Purpose : To investigate the relationship of the MPV values with the degree of sepsis and correlation MPV with procalcitonin.Method : A cross sectional study was conducted. The subject with infection was treated in ward or Intensive Care Unit (ICU) in Adam Malik General Hospital, after fulfilling the inclusion criteria, full blood examination including MPV, procalcitonin, blood cultures was taken. The MPV values was compared between sepsis and non-sepsis, also between sepsis and severe sepsis. Then MPV values was correlated with procalcitonin.Results : Of the 50 patients with sepsis and 50 non-sepsis, found a significant difference in MPV levels of sepsis patients 10.97 (0.63) compared to the non-sepsis 9.17 (± 0.75), (p < 0.001). From the 17 patients sepsis and 33 severe sepsis patients also found a significant difference in MPV levels of severe sepsis patients 11,19 (0.64) compared with groups of sepsis patients 10.52 (0.27), (p < 0.001). And there is a strong correlation between MPV with procalcitonin r=0,702.Conclusion : The value of MPV is higher in patients sepsis and non-sepsis, and there is also a difference value of MPV in patients sepsis and severe sepsis. And also found there is correlation between MPV and procalcitonin.Keywords : sepsis, severe sepsis, mean platelet volume.